Moderasi Beragama dalam Tafsir Pesantren: Analisis Resepsi Eksegesis ‎dan Konstruksi Epistemologi Tafsir pada Pesantren di Jambi - Hasbullah, Hasbullah; Syachrofi, Muhammad; Haitomi, Faisal; Darmadi, Darmadi (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This research is motivated by the fact that acts of violence in the name of religion are mostly carried out by groups associated with Salafi pesantren (Islamic boarding schools). Some pesantren have become fertile ground for the spread of radical ideologies. On the other hand, radical understandings are often born from a literal reading of religious texts, one that disregards context. Therefore, this study aims to critically examine the understanding and interpretation of religious texts by the elites of Pesantren Salafiyah Depati Agung and Pesantren Sa’adatuddarein, particularly those texts that are frequently used as a foundation in discourses on religious moderation. The texts in focus are QS. Al-Baqarah [2]: 143 and 256. This study will also analyze the epistemological constructs behind their interpretations. This research uses qualitative methods with data collection techniques including interviews and documentation. The theoretical framework applied is the theory of exegesis reception, which involves understanding the Qur'an by interpreting its message based on linguistic meaning. To further analyze the construction of their interpretations of these verses, the study employs an epistemological theory of interpretation, which examines the sources, methods, approaches, patterns, and characteristics of interpretation. The findings of this study are as follows: First, the elites of Pesantren Salafiyah Depati Agung interpret QS. Al-Baqarah [2]: 143 and 256 as legitimizing the view that Ahlussunnah wal Jama’ah is a moderate group within the Muslim community, represented in Indonesia by Nahdlatul Ulama. In contrast, the elites of Pesantren Sa’adatuddarein do not attempt to link these verses to any particular group or sect. According to them, these verses speak to the superiority of the Muslim community over previous religious communities. Second, an epistemological analysis reveals that the elites of Pesantren Salafiyah Depati Agung tend to interpret the texts through reason (bi al-ra’y), with an ijmali-contextual method and approach. The tone and characteristics of their interpretation are theological-sectarian. Meanwhile, the elites of Pesantren Sa’adatuddarein tend to follow a bi al-ma'tsur approach, using ijmali-textual methods and approaches, with a theological-normative tone in their interpretations.